Faktor – Faktor yang Mempengaruhi Partisipasi Masyarakat dalam Pelaksanaan Program Corporate Social Responsibility (CSR) - Siti robiah nurbaiti; Aziz nur bambang (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The business world is one of the activities that encourage the success of development, which currently not only leads to economic activities to gain profit for the sustainability of the company, but also care about the social and environmental aspects of the surrounding community. The effort that has been implemented as a form of corporate social responsibility is through Corporate Social Responsibility (CSR) program that implements sustainable development known as people, profit, and planets or Triple Bottom Line (TBL) concept. In Indonesia the concept of CSR has been accepted and implemented by various companies in the field of economy, health, education and environment. Implementation of CSR program is one form of community development, where the success of the program, among others, depends on the active involvement of the community in each stage of the CSR program. Participation, then the community will feel to have the program, the higher the participation rate the greater the sense of ownership, responsibility, and contribution given to achieve the goals and success of the program. This paper is a literature review to get an overview of the factors that influence community participation in the implementation of CSR programs based on the literature and previous research results that have been implemented